2009
DOI: 10.1088/1674-1056/18/3/032
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Gauss–Bessel beams in turbulent atmosphere

Abstract: This paper studies the propagation properties of Gauss-Bessel beams in a turbulent atmosphere. Based on the extended Huygens-Fresnel principle, it derives the intensity distribution expression for such beams propagating in a turbulent atmosphere. Then the influence of turbulence and source beam parameters on the beam propagation is studied in great detail. It finds that the intensity distribution of Gauss-Bessel beams will change into Gaussian profile in a turbulent atmosphere, and that stronger turbulence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…As a result, it has been suggested that Bessel beams [18] and Airy beams [14,19] could be useful for remote sensing or directed energy applications. If the desirable properties of Bessel and Airy beams are to be harnessed for these applications, they must be robust to phase distortions resulting from atmospheric turbulence [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it has been suggested that Bessel beams [18] and Airy beams [14,19] could be useful for remote sensing or directed energy applications. If the desirable properties of Bessel and Airy beams are to be harnessed for these applications, they must be robust to phase distortions resulting from atmospheric turbulence [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The complex amplitude of a fundamental Bessel optical beam Eðx; RÞ at the observation point fx; Rg is described by a paraxial wave equation, where x is the distance between the source plane and the observation plane, and R is the vector that determines the distance between the observation point and the optical axis of the laser beam in a plane normal to the radiation propagation direction. Using the extended Huygens-Fresnel principle 12 for the secondorder mutual coherence function of the optical beam field, the mean field intensity of the fundamental Bessel optical beam propagating in a turbulent atmosphere can be written as [12][13][14][15]17 hIðx;RÞi¼hEðx;RÞE Ã ðx;RÞi…”
Section: Basic Determinationsmentioning
confidence: 99%
“…In this regard, research of the features of propagation in a turbulent atmosphere for the Bessel and Bessel-Gaussian beams is vigorously performed. [13][14][15][16][17][18][19][20][21] The majority of these works [13][14][15][16][17] is devoted to the analysis of various aspects of the behavior of the mean intensity of coherent 13,16,17 and partially coherent 14 BesselGaussian beams in randomly inhomogeneous media. In these researches, special attention is given to preservation consideration (or changes) during the propagation of topological structure of Bessel-Gaussian beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One popular example is light tailored to have an azimuthally varying phase of the form exp(i φ) with integer topological charge (TC) for of orbital angular momentum (OAM) per photon [6][7][8]. Although it is understood that other orthogonal mode sets are equally valid, including using the full radial and azimuthal indices of the Laguerre-Gaussian (LG) modes [9][10][11] as well as Bessel [12][13][14][15][16][17][18][19][20], Hermite-Gaussian [21][22][23] and vectorial modes [24][25][26][27], OAM has become the mode of choice in the majority of communication studies [28,29].…”
Section: Introductionmentioning
confidence: 99%